Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1063/1.3075547
|View full text |Cite
|
Sign up to set email alerts
|

A versatile and reliably reusable ultrahigh vacuum viewport

Abstract: We present a viewport for use in ultrahigh vacuum (UHV) based upon the preflattened solder seal design presented in earlier work [Cox et al., Rev. Sci. Instrum. 74, 3185 (2003)]. The design features significant modifications to improve long term performance. The windows have been leak tested to less than 10(-10) atm cm(3)/s. From atom number measurements in an optical dipole trap loaded from a vapor cell magneto-optical trap inside a vacuum chamber accommodating these viewports, we measure a trap lifetime of 9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Consequently, there is a considerable interest in developing a versatile UHV chamber design that can be used without concerning the eddy current and with a better optical access. In addition, many studies [5][6][7][8] have also reported the development of the reusable, removable and bakeable viewports for UHV applications, because the specifications of the viewports for UHV are gradually more demanding. Some examples, such as transmission at a wider range of wavelengths, ultra-low reflectivity, and extremely optical flatness are necessary for some specific experiments, which makes commercial viewports unable to meet the current needs.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a considerable interest in developing a versatile UHV chamber design that can be used without concerning the eddy current and with a better optical access. In addition, many studies [5][6][7][8] have also reported the development of the reusable, removable and bakeable viewports for UHV applications, because the specifications of the viewports for UHV are gradually more demanding. Some examples, such as transmission at a wider range of wavelengths, ultra-low reflectivity, and extremely optical flatness are necessary for some specific experiments, which makes commercial viewports unable to meet the current needs.…”
Section: Introductionmentioning
confidence: 99%
“…This large discrepancy in the PSF arises due to the imperfections in the optical quality of the viewport, as the full clear aperture of the window is used with substantial reduction in the optical flatness around the edges of the glass to metal seal. Improved results are possible either by post-selecting viewports or using home-made viewports from optical flats 14,15 . This does not affect the ATOM objective as this uses a larger viewport.…”
Section: Performancementioning
confidence: 99%
“…Applications, such as ellipsometry, 3 polarimetry, 4 and some optical build-up cavities, 5 require precise control over the polarization of laser beams that pass through vacuum windows. Indium gaskets are then preferred, at the cost of limiting baking temperatures to 149 • C. [6][7][8] Building on this earlier work, we have devised an indium seal scheme that can be used without modifying a ConFlat R (CF) vacuum chamber and that gives a birefringence, n = 2.3 × 10 −7 . This is more than two orders of magnitude lower than when we use copper knife edge gaskets and more than an order of magnitude lower than when we make indium seals to a standard CF flange.…”
mentioning
confidence: 99%
“…The tendency of the bolts to loosen with such small torques was avoided by using conical shaped washers. 8 We remove the flanged windows from the leak detector to measure their stress-induced birefringence. The fractional transmission, T, of a 1 mm diameter linearly polarized 1064 nm laser beam through a Glan-laser prism is first minimized, to a level of 5 × 10 −6 .…”
mentioning
confidence: 99%